Exploring the role of open book high-stakes examinations in 2021 and beyond - Cummings, Beth-Ann (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2022)
Performance on medical licensing examinations has been previously shown to be predictive of performance in practice. However, licensing examinations are closed-book and real-world medical practice increasingly requires doctors and patients to consult resources to make evidence-informed decisions. To best assess the ability of physicians and physicians-in-practice to avail themselves of point-of-care clinical resources and tools, open-book components may have an emerging role in high-stakes examinations.